ZAC in GtoPdb v.2023.1 - Davies, Paul; Hales, Tim G.; Jensen, Anders A.; Peters, John A. (IUPHAR/BPS Guide to Pharmacology CITE, 2023)
The zinc-activated channel (ZAC, nomenclature as agreed by the NC-IUPHAR Subcommittee for the Zinc Activated Channel) is a member of the Cys-loop family that includes the nicotinic ACh, 5-HT3, GABAA and strychnine-sensitive glycine receptors [2, 3, 5]. The channel is likely to exist as a homopentamer of 4TM subunits that form an intrinsic cation selective channel equipermeable to Na+, K+ and Cs+, but impermeable to Ca2+ and Mg2+ [5]. ZAC displays constitutive activity that can be blocked by tubocurarine, TTFB and high concentrations of Ca2+ [5]. Although denoted ZAC, the channel is more potently activated by H+ and Cu2+, with greater and lesser efficacy than Zn2+, respectively [5]. Orthologs of the human ZACN gene are present in a wide range of mammalian genomes, but notably not in the mouse or rat genomes. [2, 3].